KLARIFIKASI KEMATANGAN BUAH NANAS DENGAN RUANG WARNA HUE SATURATION INTENSITY (HSI) - Budi Yanto; jufri jufri; Adyanata Lubis; B.Herawan Hayadi; Erna Armita, NST (P3M Politeknik Negeri Bengkalis, 2021)
Pineapple fruit is included in the type of tropical fruit, which is quite popular because it contains a lot of Vitamin C, which is quite high. Pineapple is a local fruit in the Kampar area, this fruit can be consumed directly and become other local processed products. Therefore, the quality of pineapple ripeness must be maintained. The problem that occurs at this time is that the pineapple fruit selection process is still done manually, by looking at it visually, so mistakes can occur in the process of clarifying pineapple fruit identification according to standards. Therefore, it is necessary to research the ripeness of pineapples using the Color Space Algorithm Hue Saturation Intensity (HIS). The variables to be input are based on photos of ripe, half ripe, and raw pineapples using a smartphone camera or DSLR camera with a minimum resolution of 8 MP. Clarifying the results with image processing and Hue Saturation Intensity (HIS) transformation has an accuracy rate of 80% for the 20 image test data. So that the expected results can help pineapple farmers in detecting the level of maturity of pineapple fruit, which is difficult, can minimize errors in determining the ripeness of pineapple fruit